Praktik Khiyār dalam Transaksi Tiket Transportasi Shuttle: Studi Kasus Baraya Travel - Irfan Maulana; Muhammad Saepul Ulum; Rizal Muttaqin (Al-fiqh, 2026)
In the context of Baraya Travel, the dynamics of shuttle ticket transactions often reveal consumer misunderstandings regarding terms and conditions for cancellations, which may undermine the integrity of the contract. This study is field research employing a descriptive-analytical qualitative approach. Data were collected through observations and documentary studies, then analyzed using the principles of Islamic Economic Law. The findings indicate that the transaction mechanism at Baraya Travel normatively provides for khiyār rights, particularly through the company’s established ticket cancellation policies. However, empirically, an information gap persists where consumers lack a comprehensive understanding of these standard clauses. The analysis of Islamic Economic Law confirms that khiyār practices at Baraya Travel align with muamalah principles, where renegotiation or mediation serves as a solution to achieve benefit (maslahah). This study suggests the importance of transparency and education regarding the contract at the outset of the transaction to ensure that the fulfillment of rights and obligations between the service provider and user is fully realized in accordance with Sharia principles.